Development of educational-use computational fluid dynamics programming environment and workshop. (June 2016) - Nakano, Akito; Bohn, John N; Wakita, Akira
In the current computer-aided architectural design education, students do not necessarily need to be taught to use more digital tools, but need to be introduced to the possibilities of designing their own digital tools. Designing the original tools with the assistance of educational-use environment for computational fluid dynamics programming improves the capability of the students to estimate the flows around architectures based on the mathematical background and the actual program. The authors have developed Educational Library for Fluid as an educational-use environment for computational fluid dynamics programming and ran the workshop where the students majoring in computer-aided architectural design tried to design computational fluid dynamics tools with Educational Library for Fluid. In this article, the details of Educational Library for Fluid and the results of the workshop are being reported. In addition, the key points of computational fluid dynamics education that the authors learned through the experience of the workshop are shared.